The Emergence of Biolaw The European Experience and the Evolutionary Approach - Vidalis, Takis (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book introduces "biolaw" as an integrated and distinct field in contemporary legal studies. Corresponding to the legal dimension of bioethics, the term "biolaw" is already in use in academic and research activities to denote legal issues emerging mostly from advanced technological applications. This book is a genuine attempt to rationalize the field of biolaw after almost four decades of continuous production of relevant legislation and judgments worldwide. This experience is a robust basis for defending a) a separate legal object, covering the total of legal norms that govern the management of life as a natural phenomenon in all its possible forms, and b) an "evolutionary" approach that opens the discussion on a future conciliation of legal regulation with the Theory of Evolution on the ground of biolaw.
A General Introduction -- Part I: Persons -- Introduction - The Concept of Biological Autonomy -- Pathology -- Research -- Death -- Data -- Reproduction -- Enhancement -- Self-ownership -- Part II: From Biodiversity To Intelligent Machines -- Introduction: Biodiversity as a Legal Value -- The Conservation of Species -- The Creation of Species -- Life as commodity -- Concluding Remarks -- Future Challenges for Biolaw -- "Animal rights" -- Biolaw beyond Biology: Artificial Intelligence and Smart Robots.
Keywords: Medical laws and legislation; Human rights; Bioethics; Law-Europe.; Private international law; Conflict of laws; International law; Comparative law; Medical Law; Human Rights; Bioethics; European Law; Private International Law, International and Foreign Law, Comparative Law